Chico Pinto e os Autênticos do MDB: atuação no campo político brasileiro (1971-1982) - Souza, Flávia Amorim (2013)
This work has as its goal the study of Francisco Pinto's political journey as a member of the so-called group Autênticos do Movimento Democrático Brasileiro (MDB) in Brazilian National Congress, in his taking of a contrary posture to the civilian/military dictatorship, in his actuation in Brazilian political field in the period between 1971 and 1982. This time corresponds to the period in which Francisco Pinto was a federal congressist: his first term in 1971-74, impeachet in 1974, and second, 1979-82. We investigated how the congressman and his Autênticos group built an opposite force to the dictatorship. For that, we used sociologist Pierre Bourdieu's method, of political camp, so we can understand the strategies and possibilities of making institutional politics. The sources consulted were: congressman Francisco Pinto speeches in Brazilian National Congress and Movimento newspaper.